KEPERCAYAAN DIRI MAKE UP ARTIST PRIA - Yunita Arthavia; Mochamad Widjanarko (Jurnal Riset Psikologi, 2025)
Men can do the MUA profession because they have feminine traits in their personality but need to make adjustments when carrying out their work, so self-confidence is required to support their success as male makeup artists.This study intends to analyze the factors that influence self-confidence in male MUA with a qualitative phenomenological and snowball sampling. The collected data were coded into categories as analysis. So the results obtained from the first informant's internal factors that stand out more than external factors are physical condition factors. For the second informant, the external factor makes this factor more prominent than the internal factor is environmental factors. The third informant also, the internal factor is the self-concept factor makes it more prominent than external factors. So that further researchers can consider the existing weaknesses.